Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/nano10050861
|View full text |Cite
|
Sign up to set email alerts
|

Ag2S QDs/Si Heterostructure-Based Ultrasensitive SWIR Range Detector

Abstract: In the 20th century, microelectronics was revolutionized by silicon—its semiconducting properties finally made it possible to reduce the size of electronic components to a few nanometers. The ability to control the semiconducting properties of Si on the nanometer scale promises a breakthrough in the development of Si-based technologies. In this paper, we present the results of our experimental studies of the photovoltaic effect in Ag2S QD/Si heterostructures in the short-wave infrared range. At room temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…[53] However, it is interesting that the present MSM type photodetectors based on the Ag 2 HgS 2 SCRs show linear responses, and they perform equivalent and high responsivities compared with most high-level van der Waals heterojunction photodetectors. [62][63][64][65] In fact, it is also worth noting that the Ag 2 HgS 2 SCRs photodetectors perform better than the InGaAs photodetectors (PDA20C2, Thorlabs, effective wavelength range between ≈800 and 1700 nm, Responsivity = 1 A W −1 , NEP = 2.2 × 10 −11 W Hz −1/2 ) and PbSe photodetectors (PDA20H, Thorlabs, NEP = 1.5 × 10 −10 W Hz −1/2 ) that have been commercially used. The investigations illustrate that the as-made Ag 2 HgS 2 -based photodetectors with extraordinary performance are highly potential for practical applications, especially in weak light photodetection including infrared regions in the future since Ag 2 HgS 2 is an alternatively promising and qualified candidate due to its intrinsic property and excellent photodetecting behavior.…”
Section: Resultsmentioning
confidence: 99%
“…[53] However, it is interesting that the present MSM type photodetectors based on the Ag 2 HgS 2 SCRs show linear responses, and they perform equivalent and high responsivities compared with most high-level van der Waals heterojunction photodetectors. [62][63][64][65] In fact, it is also worth noting that the Ag 2 HgS 2 SCRs photodetectors perform better than the InGaAs photodetectors (PDA20C2, Thorlabs, effective wavelength range between ≈800 and 1700 nm, Responsivity = 1 A W −1 , NEP = 2.2 × 10 −11 W Hz −1/2 ) and PbSe photodetectors (PDA20H, Thorlabs, NEP = 1.5 × 10 −10 W Hz −1/2 ) that have been commercially used. The investigations illustrate that the as-made Ag 2 HgS 2 -based photodetectors with extraordinary performance are highly potential for practical applications, especially in weak light photodetection including infrared regions in the future since Ag 2 HgS 2 is an alternatively promising and qualified candidate due to its intrinsic property and excellent photodetecting behavior.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Combinations of two dissimilar materials to form heterostructures have been widely demonstrated. 21 Tretyakov et al 22 reported a Ag 2 S QD/Si heterostructure short-wave infrared photodetector. Xie et al 23 introduced a MoTe 2 /CsPbBr 3 heterojunction photodetector.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Apart from the above applications, in recent years, more and more attention has been focused on its potential application in photodetectors due to their near-infrared transparency, low cost, nontoxicity and compatibility with silicon integrated circuits. [18][19][20] Kang et al prepared a photodetector by assembling Ag 2 S nanoparticles on the silicon oxide substrate and covering a layer of graphene on the top of Ag 2 S nanoparticles. They found that the photodetector showed a high photoresponse of 2723.2 A W À1 under 550 nm illumination with 0.89 mW cm À2 .…”
Section: Introductionmentioning
confidence: 99%
“…They found that their photodetector is highly sensitive to wavelengths from 400 nm to 1100 nm and the response is fast, less than 5 ms. 22 Ismail et al and Tretyakov et al prepared Ag 2 S/Si heterojunction photodetectors. 20,23 Ismail et al found that the properties of the detector were dependent upon the Ag 2 S nanotube deposition time and the maximum responsivity was found to be ca. 0.5 A W −1 at 850 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation